GAMBARAN PENGETAHUAN DAN TINGKAT KEMANDIRIAN PENGAWAS MINUM OBAT (PMO) DALAM PERAWATAN PASIEN TUBERKULOSIS (TB) DI PUSKESMAS NUSA INDAH KOTA BENGKULU - Try Mika Panidah (Universitas Bengkulu, 2022)
Tuberculosis (TB) is an infectious infectious disease caused by the bacterium Mycobacterium tuberculosis. Drug taking supervisor (PMO) is a person or family in charge of direct supervision of pulmonary TB patients when taking medication every day based on short-term medication guidelines. PMO knowledge is a collection of information obtained by a person about TB, such as what TB is, how to treat it and how it is transmitted to prevent TB disease. PMO independence is the ability to decide and take an action independently or without the help of others. The ability in question is the person's effectiveness in doing all kinds of work. The purpose of this study was to describe the knowledge and level of independence of drug-taking supervisors (PMO) in the care of tuberculosis (TB) patients. This type of research uses quantitative descriptive analysis, the sample technique used is total sampling, with 23 respondents as research respondents. The results showed good knowledge as much as 95.65%, sufficient knowledge as much as 4.35% and the level of independence of the respondents obtained independent results as much as 86.96%, and those who were not independent as much as 13.04%. The conclusion in this study is that the knowledge and level of independence of PMO is very influential for the care of TB patients at home, because of their duties and roles in carrying out care. The importance of knowledge and the level of independence for the role of PMO can increase the cure rate of TB patients and reduce the mortality rate caused by TB disease